PENERAPAN TATA CARA PENCABUTAN PENGUKUHAN PKP SESUAI PERATURAN DIITJEN PAJAK NOMOR 12 TAHUN 2014 PADA KPP PRATAMA MANADO - Mangare, Virgie (ACCOUNTABILITY, 2015)
Tax is playing important role in economy of the country. Today, number of firms from big to small many have not been listed to KPP Pratama Manado. Directorate General of Taxation Â Issues rule No.12 Tahun 2014 in order to grouping the sales limit and simplified the administration and controlling. Many business sector listed but have not been revocation and have sales under Rp. 4,8 Billion. The purpose if this research is to knowing that the application of rules Directorate General of Taxation No.12 Tahun 2014. Data analysis method uses is descriptive. To know the limit of the sales it need income statement. Tax fare and calculation method of income tax. The difference of tax which is deposited is quite large. The application of PP No.46 Tahun 2013 is really profitable because income tax which must be deposited is much smaller. Meaning the new rules is much simpler, and to make the government more easier to grouping the sales limit and the revocation of taxable enterprise. To improve service and improve administratif simplification as well as controling. KPP Pratama Manado should be more sosializing the new regulations.